2005
DOI: 10.2337/diabetes.54.3.702
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Secretory Dysfunction in the Pathogenesis of Low Birth Weight–Associated Diabetes

Abstract: Low birth weight (LBW) is an important risk factor for type 2 diabetes. We have developed a mouse model of LBW resulting from undernutrition during pregnancy. Restriction of maternal food intake from day 12.5 to 18.5 of pregnancy results in a 23% decrease in birth weight (P < 0.001), with normalization after birth. However, offspring of undernutrition pregnancies develop progressive, severe glucose intolerance by 6 months. To identify early defects that are responsible for this phenotype, we analyzed mice of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 52 publications
6
124
2
1
Order By: Relevance
“…The pancreas is a plastic organ, and early life events may play a role in determining the capacity for adult pancreatic plasticity. Several animal models have demonstrated altered pancreatic development following in utero deprivation [67][68][69][70]. A group of imprinted genes including Igf2, Rasgrf, Grb10, Neuronatin and Zac1 play key roles in pancreatic development and maturation and may be involved in the pathogenesis of these defects, although direct evidence of this remains scanty.…”
Section: Imprinted Genes and The Pancreatic Consequences Of In Utero mentioning
confidence: 99%
“…The pancreas is a plastic organ, and early life events may play a role in determining the capacity for adult pancreatic plasticity. Several animal models have demonstrated altered pancreatic development following in utero deprivation [67][68][69][70]. A group of imprinted genes including Igf2, Rasgrf, Grb10, Neuronatin and Zac1 play key roles in pancreatic development and maturation and may be involved in the pathogenesis of these defects, although direct evidence of this remains scanty.…”
Section: Imprinted Genes and The Pancreatic Consequences Of In Utero mentioning
confidence: 99%
“…Twenty-six studies reported on protein restriction, one using a mouse model [4], and twenty-five using a rat model . Twenty-four reported on general (caloric) undernutrition, one study using guinea pigs [30] and two on a mouse model [31,32], five using a sheep model [33][34][35][36][37] and 16 studies on rats [7,8,13,[38][39][40][41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Resultsmentioning
confidence: 99%
“…Randomization was reported in twenty-four studies, either randomization to the dietary regimen or randomly selecting the pups that were studied from the litters [14,15,[17][18][19][20][21][22][23][24]26,28,29,31,32,[34][35][36]39,42,44,48,50,[52][53][54]. None of the studies reported a sample size calculation or methods for concealment of allocation.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Self-sustaining loops and structural inheritance also impact epigenetic events but these mechanisms are less understood and will not be discussed in length in this article. Instead, the focus will remain on how DNA methylation, histone modifications, and noncoding RNA act in concert to make molecular modifications to DNA contributing to disease susceptibility and expression [10,30,31].…”
Section: Specific Epigenetic Mechanismsmentioning
confidence: 99%